Pendampingan Manajemen Waktu Berbasis Self-Regulated Learning pada Siswa SMP - Firda, Amaral; Afrina; Morningrum, Roro Dewila; Rahmawati, Siti; Azzahrah, Iqrima; Salsabila; Supyan; Djihadah, Nuryati (CV. Kurnia Grup, 2026)
The rapid development of digital technology provides students with easy access to information but also creates challenges in managing study time, which affects learning independence. This community service activity aims to improve students’ learning independence through time management assistance based on Self-Regulated Learning. The method used was a participatory approach through lectures, discussions, question-and-answer sessions, and practical exercises in learning planning. The implementation stages included preparation, execution, and evaluation. The results showed significant improvements across several indicators: students’ understanding of time management increased from 65% to 80%, their ability to create structured study schedules improved from 70% to 85%, and their learning independence rose from 75% to 90%. These findings indicate a consistent increase of 15 percentage points across all indicators. In addition, students demonstrated more disciplined and responsible behavior toward academic tasks. Therefore, Self-Regulated Learning-based assistance is effective in enhancing students’ learning independence in the digital era.